Applying Cryptographic Algorithm in C language : A Matrix-Based Approach to Securing Data - Nair, Seema; Jog, Amruta (Indian Journal of Computer Science, 2024)
In today's digital era, the significance of Cryptography in Cybersecurity has grown tremendously. Cryptography is vital for safeguarding sensitive information and enabling secure communication even in the presence of potential threats. By securing data exchanges over untrusted networks such as the Internet, Cryptography protects online transactions, personal data, and confidential communication, thereby reinforcing digital trust. The present paper explores the evolution of Cryptography from its historical roots to its modern applications in digital communication security. While highlighting the mathematical principles behind Cryptographic algorithms, our focus shifts to the practical implementation of encryption and decryption using the C programming language. Based on matrices, the algorithm is executed in C language to showcase its real-world applicability. Various examples are presented to validate the code alongwith a discussion of its limitations and the potential for expanding its scope in future research. Though the current implementation is restricted to 3-dimensional invertible square matrices, the approach can be scaled to accommodate any n-dimensional invertible square matrix. While mathematics provides the foundation, the focus is on how C programming enables the practical implementation of cryptographic techniques in digital security.